THE PORTRAIT OF QUEER IN LOVE IS ALL YOU NEED MOVIE - Sitti Nur Ainun; Rasiah Rasiah; Halijah Koso (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2025)
This study focuses on the analysis of the representation of queer people, focusing on lesbians and gays, in the movie Love Is All You Need. It aimed to reveal the depiction of lesbians and gays as normal as the heterosexual people in real life. In analyzing the data, the writer applied descriptive qualitative research. Using both library and media research related to the study as the sources of analysis. The constructionist approach of Stuart Hall’s representation theory was utilized to analyze the movie. The director attempts to use the movie to change audiences’ perspectives towards LGBTQ people. The movie displays the depictions of lesbians and gays differently, in which they are portrayed as people who live normally in the world. The results of this study showed that the movie had normalized lesbians and gays by representing them as religious people, majority people, educated people, people with normal appearances, parents with happy children, and people with proper and high-position jobs. Moreover, it also revealed how lesbians and gays used the term ‘breeding season’ for the time in getting children.